Full coverage of a reader's interests in context‐based information filtering. (6th April 2021) - Dumitrescu, Alexandra; Santini, Simone
Abstract: We present a collection of algorithms to filter a stream of documents in such a way that the filtered documents will cover as well as possible the interest of a person, keeping in mind that, at any given time, the offered documents should not only be relevant, but should also be diversified, in the sense of covering all the interests of the person. We use a modification of the WEBSOM algorithm to create a user model based on a self‐organizing network trained using a collection of documents representative of the person's interests. We introduce the concepts of freshness and coverage . A document is fresh if it belongs to a semantic area of interest to a person for which no documents were seen in the recent past; a group of documents has coverage to the extent to which it is a good representation of all the interests of a person. Our tests show that these algorithms can effectively increase the coverage of the documents that are shown to the user without overly affecting precision.